Data structures and algorithms made easy in java : data structure and algorithmic puzzles - Karumanchi, Narasimha (CareerMonk Publications, 2018)
Introduction.--Recursion and backtracking.--Linked lists.--Stacks.--Queues.--Trees.--Priority queues and Heaps.--Disjoint set ADT.--Graph algorithms.--Sorting.--Searching.--Selection algorithms [Medians].--Symbol tables.--Hashing.--String algorithms.--Algorithms design techniques.--Greedy algorithms.--Divide and conquer algorithms.--Dynamic programming.--Complexity classes.--Miscellaneous concepts.--References.